Study on the air heating process of the injection mold for the meshing product - Pham , Sơn Minh; Do, Thành Trung; Le , Tuyên Giáo; Tran, Minh Thế Uyên (Journal of Technical Education Science, 2015)
For the injection molding process, the high mold temperature shows many advantages with the product quality. However, higher mold temperature will lead to the longer cooling time. Therefore, the external gas assisted mold temperature control (Ex-GMTC) is presented for raising the mold surface temperature in the filling step, and let the cooling step doesnot too long. In this research, the Ex-GMTC was achieved with a real mold. The experimental results show that, with the local heating area, when the gas temperature rose from 200 oC to 400oC, the stable temperature of the mold surface increased from 90oC to 160oC. By simulating with ANSYS CFX, the heating process could be predicted within the the error was lower than 10oC. Besides, the mold temperature of the local heating could be observed clearly based on the numerical analysis.